Multiplex diagnostics : development of serological dualmode multiplex microarray immunoassay and analysis of influenza and respiratory syncytial virus disease burden in early childhood - Kazakova, Anna (fi=Turun yliopisto|en=University of Turku|, 2019)
Respiratory syncytial virus (RSV) and influenza A (IAV) and B (IBV) viruses infect humans throughout their life with exceptionally high rates of re-infection. Serological assays are commonly used to diagnose and characterize host immune responses against microbial pathogens acquired by natural infection or vaccination. The current methods are mostly based on enzyme immunoassay (EIA) or other conventional methods in a single analyte format. Presently, there is a need to shift from single analytical methods to microarray format which enables the detection of antibodies against multiple targets in a rapid and cost-effective manner. In this study, a highly sensitive single analyte EIA method was used for serological analyses in children’s sera. In addition, multiplex microarray immunoassay (MAIA) methods were developed for rapid and simultaneous detection of IgG antibodies against seven viral antigens (H1N1pdm09 vaccine ag, IAV H1N1, IAV H3N2, IBV Victoria, IBV Yamagata, RSV and adenovirus hexon protein). We found out that MAIA is well suitable for large-scale serosurveillance and vaccine immunity studies. We followed-up virus-specific immunity by MAIA in response to natural infection and vaccination in a large cohort of 0-2 year old children. Our serological findings showed a high rate of respiratory virus infections and reinfections in young children. The applicability of MAIA in vaccine immunity studies was also analysed. We developed a specific, sensitive, sample and antigen saving assay for simultaneous detection of IgM and IgG antibodies against H1N1pdm09 vaccine ag and IBV Yamagata. MAIA showed excellent correlation with EIA and a good correlation with hemagglutination inhibition assay in measurement of vaccine-induced antibodies in sera of Pandemrix-vaccinated adults.

Respiratory syncytial virus (RSV) ja influenssa A- (IAV) ja B(IBV)-virukset ovat merkittäviä ylähengitystieinfektioiden aiheuttajia koko ihmisen elinkaaren ajan. RSV:n ja influenssan aiheuttamat infektiot voivat joskus olla vakavia tai jopa henkeä uhkaavia erityisesti pienillä lapsilla ja ikäihmisillä. Nykyiset serodiagnostiset menetelmät perustuvat entsyymi-immunologisiin (EIA) ja muihin määritysmenetelmiin, joissa immuunivastetta voidaan tutkia kerrallaan vain yhtä taudinaiheuttajaa kohtaa. Tällä hetkellä on seerumin vasta-ainetutkimusten osalta suuri tarve siirtyä monianalyyttisiin menetelmiin, jotka olisivat nopeampia ja kustannustehokkaampia kuin nykyiset tutkimusmenetelmät. Tässä tutkimuksessa on käytetty herkkiä EIA-menetelmiä pienten lasten ja influenssarokotettujen henkilöiden seerumien virusspesifisen immuunivasteen tutkimiseen. Työssä on myös kehitetty monianalyyttinen mikrosiruperusteinen immunomääritysmenetelmä (MAIA) samanaikaiseen seerumin IgG-luokan vastaaineiden mittaamiseen eri influenssavirusantigeeneja, RSV:tä ja adenoviruksen heksoniproteiinia kohtaan. Tutkimuksemme osoittivat, että hengitysteiden virusinfektiot ja yllämainittujen virusten aiheuttamat uusintainfektiot ovat erittäin tavallisia pienillä lapsilla. MAIA-menetelmää sovellettiin myös aikuisten influenssarokotevasteiden analyysiin. Menetelmää kehitettiin edelleen siten, että näytteestä voitiin samalla kertaa mitata seerumin IgG- ja IgM-luokan vasta-aineita eri IAV- ja IBV-virusantigeeneja kohtaan. Menetelmä osoittautui erittäin spesifiseksi, herkäksi ja näytettä ja antigeeneja säästäväksi ja tulokset olivat hyvin yhtenevät muiden perinteisten vasta-ainetutkimusmenetelmien kanssa. Kehittämämme MAIA-menetelmä toimi erittäin hyvin ja sen voitiin osoittaa sopivan erinomaisesti laajojen väestön seerumiaineistojen ja virusrokotevasteiden analyysiin.